A Portable and Efficient Solar‐Rechargeable Battery with Ultrafast Photo‐Charge/Discharge Rate. Issue 28 (12th June 2019) - Hu, Yuxiang; Bai, Yang; Luo, Bin; Wang, Songcan; Hu, Han; Chen, Peng; Lyu, Miaoqiang; Shapter, Joe; Rowan, Alan; Wang, Lianzhou
Abstract: The solar‐rechargeable electric energy storage systems (SEESSs), which can simultaneously harvest and store solar energy, are considered a promising next‐generation renewable energy supply system. However, the difficulty in meeting the demands of higher overall photoelectric conversion and storage efficiency (PCSE) with both high power density and large energy density in the current SEESSs severely limit their practical application. Herein, a new class is demonstrated of portable and highly efficient SEESS that uniquely integrates a perovskite solar module (PSM) and an aluminum‐ion battery (AIB) directly on a bifunctional aluminum electrode without any external circuit. Such nanostructural design in the SEESS not only exhibits fast photo‐charge/discharge rate (less than one minute) with high power density (above 5000 W kg −1 ), but also delivers a high energy density (above 43 Wh kg −1 ). By rationally matching the maximum power point voltage of PSM with AIB charging voltage, an excellent solar‐charging efficiency of 15.2% and a high PCSE of 12.04% are achieved, which is among the best in all reported portable SEESSs. Moreover, enhanced PCSE is observed as the light intensity decreases, which makes such SEESS immune from the geographical location and climate limitations for diverse practical applications. Abstract : A portable and efficient solar‐rechargeable battery is designed by integrating/matching a perovskite solar module and aluminum‐ion battery on the bifunctional aluminum layer, which delivers high power density (above 5000 W kg −1 ), high energy density, a record overall photoelectric conversion and storage efficiency of 12.04%, and robust cycling performance (only 0.18% reduction per cycle).